9514 1404 393
Answer:
12 square inches
Step-by-step explanation:
The area is given by the formula ...
A = 1/2bh
Here, the base is 6 inches and the height is given as 4 inches. Then the area is ...
A = (1/2)(6 in)(4 in) = 12 in²
The area of the triangle is 12 square inches.
_____
<em>Comment on the problem</em>
Since you are given the base and height, we presume you are intended to use the formula above. You are also given all three side lengths. If you use the appropriate formula with those, you find the area is about 15.6 square inches. (The height of this triangle is actually closer to 5.2 inches.)
The figure represents a geometry that cannot exist. With the given base and height, the side lengths should be 5, not 6.
Answer:
x = -3
Step-by-step explanation:
expand -23x + 36 = 105
subtract 36 from both sides -23x +36 -36 = 105 - 36
Simplify -23x = 69
Divid both sides by -23: -23x / - 23 = 69 / -23
x = -3
Answer:
0.75 is the answer
Step-by-step explanation:
6/8 is equivalent to 3/4
3 divided by 4 is 0.75
Since 6/8 is equivalent then it is also 0.75
Also 6/8 turn to 3/4 when both the numerator and denominator is divided by 2.
6 divided by 2 is 3
8 divided by 2 is 4
Ur gonna have to pick an equation and solve for a variable.
2x - 2y = 6
2x = 2y + 6 ...divide everything by 2 because u want x by itself
x = y + 3
now we sub y + 3 in for x in the other equation
14x - 2y = 78
14(y + 3) - 2y = 78...distribute thru the parenthesis
14y + 42 - 2y = 78...subtract 42 from both sides, cancelling the 42 on the left
-42 -42
-----------------------
14y - 2y = 36 ...simplify
12y = 36...divide by 12 on both sides, cancelling out the 12 on the left
y = 36/12
y = 3
now , we already know that x = y + 3...and we know y = 3...so sub in 3 for y and solve for x
x = y + 3
x = 3 + 3
x = 6
solution is (6,3)
it is always a good idea to check ur answer by subbing it into one or both of the equations to see if it is correct
2x - 2y = 6......(6,3)...x = 6 and y = 3
2(6) - 2(3) = 6
12 - 6 = 6
6 = 6 (correct)
so yes, ur solution is (6,3)
Answer: True
Step-by-Step Explanation:
=> 2x + 3y = -7 (Eq. 1)
=> -x = 2y (Eq. 2)
=> x = 1, y = -3
Substitute values of ‘x’ and ‘y’ in Eq. 1 :-
=> 2x + 3y = -7
= 2(1) + 3(-3) = -7
= 2 + -9 = -7
=> -7 = -7
=> LHS = RHS
Therefore, it is a Solution.